2009
DOI: 10.1051/0004-6361:200810005
|View full text |Cite
|
Sign up to set email alerts
|

Nova-like cataclysmic variable TT Arietis

Abstract: Aims. We study the variability of the nova-like cataclysmic variable TT Ari, on time-scales of between minutes and months. Methods. The observations in the filter R were obtained at the 40-cm telescope of the Chungbuk National University (Korea), 51 observational runs cover 226 h. The table of individual observations is available electronically. In our analysis, we applied several methods: periodogram, wavelet, and scalegram analysis. Results. TT Ari remained in a "negative superhump" state after its return fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…7, lower entire run, nor in limited time intervals, could we identify significant QPOs. Kim et al (2009) found occasional QPOs with mean semi-amplitudes between 1.4 and 8.2 % in the period range between 10 and 27 minutes, which apparently were not present in our MOST observations. They only show random variability in typical time scales of a about 10-20 minutes with amplitudes up to 0.1 mag (flickering).…”
Section: Frequency Analysiscontrasting
confidence: 74%
See 1 more Smart Citation
“…7, lower entire run, nor in limited time intervals, could we identify significant QPOs. Kim et al (2009) found occasional QPOs with mean semi-amplitudes between 1.4 and 8.2 % in the period range between 10 and 27 minutes, which apparently were not present in our MOST observations. They only show random variability in typical time scales of a about 10-20 minutes with amplitudes up to 0.1 mag (flickering).…”
Section: Frequency Analysiscontrasting
confidence: 74%
“…Between 1986 and 1996 several authors (Skillman et al 1998;Andronov et al 1999;Kraicheva et al 1999) (Skillman et al 1998;Wu et al 2002;Andronov et al 2005). In October 2005 the negative superhumps had reappeared: Kim et al (2009) A preliminary analysis of these data reveals a rather stable superhump period P S = 0.132883±0.000003 d (Vogt et al, in preparation), within the range of the historical observations between 1961 and 1988. Therefore, the superhump period presented here for October/November 2007 is larger than any other value known before or after the MOST run.…”
Section: Discussionmentioning
confidence: 69%
“…BT Mon and V533 Her; Warner 2004). But here again there is similarity between V842 Cen and TT Ari – the latter has QPOs extending over the range 900–1500 s (Kim et al 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Photometric observations at the beginning of July 2009 show that the star's brightness, R~11 m .21 [20], corresponds to the normal brightness of the star in its "negative superhump" phase [21]. [13,14].…”
Section: Observational Resultsmentioning
confidence: 99%